Unmet Need of Postpartum Contraceptives Use in Urban Slums: Unmet need of postpartum contraceptives (Journal of Preventive and Social Medicine, 2020)
Background: Unwanted pregnancy is common in slum dwelling couples as they are less aware about postpartum contraceptive. Unmet need of postpartum contraceptive is also evident in slums.Objective: This study aims to assess the unmet need of post-partum contraceptives used in urban slums.Materials and Methods: This study was a cross-sectional study on fecund women in postpartum period (0 months to 24 month). A total of 162 postpartum women were face to face interviewed with a pretested semi structured questioner by using software SPSS- 20.Place and period: The study was conducted in slum area of Jurain and Moghbazar in Dhaka city, during the period of January 2016 to December 2016.Results: About 51.2% (83) of the respondents were in the age group of 22-26 years. Almost 53.1% (86) of the respondents were illiterate. 57.4% (93) of the respondents were housewife. 61.1% of the respondents gave history of monthly family income of 4200-5700 taka. Total unmet need of postpartum contraceptive period, among 162 respondents were 58% about 94 and met need 42% (68). Intention for contraceptives used, were 86% (81) among 94 respondents. Factors related with unmet need – All most 45.7% of the respondents were not used any contraceptives due to not approved by their husband among 94 respondents. Decision regarding family planning has given by husband 51.85% (84). There were significant association with education and unmet need of contraceptives use (p